AKSI BERSIH PANTAI SEBAGAI UPAYA MENINGKATKAN KEPEDULIAN MASYARAKAT DALAM MENJAGA KEBERSIHAN PANTAI KUTA, PROVINSI BALI - Husnayaen; Arini, Dwi Puspa; Anhar, Alfian; Bela, Riyani; Widnyana, I Made Alit; Pamungkas, Angger Bayu (Universitas Mataram, 2024)
The waste accumulation problem is no longer a new problem at Kuta Beach. Various efforts have been made by society and local government to reduce existing pollution. However, these efforts are still unable to reduce the huge rubbish problem at Kuta Beach. The phenomenon of the west wind that sends rubbish from outside Bali and the society’s lack awareness in protecting the environment worsen the beauty of Kuta Beach. This waste problem threatens Kuta Beach in terms of beauty, public health and the biota around it. One effort that can be made to overcome this problem is by carrying out beach clean-up activities around Kuta Beach. This beach clean-up action aims to provide understanding to the local community and tourists about the importance of maintaining cleanliness so that the beauty of Kuta Beach can be enjoyed comfortably. The implementation of this beach clean-up action received the attention of many parties and was attended by 1798 participants consisting of various groups of people from children to adults. The beach clean-up activity was well organized and ran smoothly in accordance with the activity plan that had been prepared.